(untitled) (Third Sector Social Economic Review, 2025)
Agricultural subsidies are not only instruments to increase production at the sectoral level but also important public policy tools that affect growth dynamics at the macroeconomic level. In this context, public interventions in the sector can contribute to the growth process both directly and indirectly by influencing resource allocation. This research investigates at how agricultural subsidies, gross fixed capital formation, government final consumption expenditures, inflation, and agricultural output affect economic growth in Türkiye from 1990 to 2023. The Johansen Cointegration technique was employed in this research to find the long-term connection between the variables. Also, the FMOLS, CCR, and DOLS techniques were used to figure out the direction and coefficients of the cointegration relationship. Here are the main results of the study: (i) The variables stay the same at their first differences; (ii) The series show a long-term cointegration relationship; (iii) The FMOLS, DOLS, and CCR methods show that higher agricultural subsidies, gross fixed capital formation, government final consumption expenditures, and inflation all help the economy grow.